Concomitant Chemoradiotherapy With Image-guided Pulsed Dose Rate Brachytherapy as a Definitive Treatment Modality for Early-stage Cervical Cancer. (June 2015) - Refaat, Tamer; Castelain, Bernard; Small, William; Elsaid, Amr; Lotfy, Nashaat; Lartigau, Eric; Nickers, Philippe
<x xml:space="preserve">Abstract</x> Purpose: Concurrent chemoradiotherapy (CRT) is the standard of care for patients with bulky cervical cancer. This study aimed to determine the feasibility, tolerance, and effectiveness of pulsed dose rate (PDR) image-guided brachytherapy (IGBT), utilizing magnetic resonance imaging (MRI) planning after CRT for stages IB2 and II cervix cancer patients. Methods and Materials: This study planned to include patients with histologically confirmed stage IB2 and II cervical cancer who were treated with CRT followed by a PDR IGBT boost from January 2009 to December 2009 in our institution. All patients had at least a partial response after CRT before IGBT. The institutional review board approved the study. Patients received a 45-Gy external beam radiotherapy (EBRT) to the pelvis with concomitant weekly cisplatin (40 mg/m2) for 5 cycles. All patients then underwent reimaging using MRI before BT. The IGBT boost was accomplished with one insertion using an MRI-compatible tandem and ovoid applicator delivering 30 to 35 Gy to a high-risk clinical target volume. Treatment-induced adverse events (AEs), dose parameters, local control, progression-free survival, and overall survival are reported. Results: Forty patients were included in this study, with ages ranging from 31 to 65 years (median age, 45 y). Of all the patients, 12.5% and 5% experienced grade 3 to 4 acute gastrointestinal and genitourinary AEs, respectively, and 2.5% and 2.5% had grade 3 to 4 chronic gastrointestinal and genitourinary AEs, respectively. Within a median follow-up of 30 months (range, 7 to 40 mo), local control was 90%, progression-free survival was 87.5%, and overall survival was 100%. Conclusions: Intracavitary MRI PDR-IGBT boost after CRT is a feasible, tolerable, and effective treatment modality for patients with stages IB2 and II cervical cancer.